2016
DOI: 10.3389/fpls.2016.00569
|View full text |Cite
|
Sign up to set email alerts
|

Fruit Calcium: Transport and Physiology

Abstract: Calcium has well-documented roles in plant signaling, water relations and cell wall interactions. Significant research into how calcium impacts these individual processes in various tissues has been carried out; however, the influence of calcium on fruit ripening has not been thoroughly explored. Here, we review the current state of knowledge on how calcium may impact the development, physical traits and disease susceptibility of fruit through facilitating developmental and stress response signaling, stabilizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
193
0
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 293 publications
(210 citation statements)
references
References 165 publications
(258 reference statements)
3
193
0
14
Order By: Relevance
“…Hocking et al . suggested that loss of firmness likely involves modification of pectin side chains, depolymerization of apoplasmic calcium–pectin crosslinks and degradation of cell wall polysaccharides.…”
Section: Discussionmentioning
confidence: 99%
“…Hocking et al . suggested that loss of firmness likely involves modification of pectin side chains, depolymerization of apoplasmic calcium–pectin crosslinks and degradation of cell wall polysaccharides.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that, compared with the control, the three tested Ca‐containing foliar fertilizers influenced the Ca content and N/Ca ratio of bagged apple fruits much more than the fruit N content, leaf Ca content, leaf N content and N/Ca ratio of leaf (Figs and ). The results showed that the tested Ca fertilizers containing CaCl 2 , Ca(NO 3 ) 2 and especially Ca(HCOO) 2 could help to supply much more Ca nutrient to the bagged apple fruits, confirming there was much higher Ca content in leaves than in fruits, and a lower rate of nutrients supplied to fruits, which indicated that the three tested Ca‐containing foliar fertilizers could potentially improve the quality of bagged apple fruits by improving the distribution of the mineral nutrients in bagged apple fruits and the rest of the apple plant.…”
Section: Discussionmentioning
confidence: 93%
“…The Ca content is generally much higher in leaves, which have greater transpiration rates than do fruits, because Ca is imported into fleshy fruits only in small amounts . The rate of water supply and nutrients to fruits is lower than to the rest of the plant, and Ca 2+ delivery to organs depends on the concentration of Ca 2+ in the xylem sap, transpiration and growth rate …”
Section: Discussionmentioning
confidence: 99%
“…In addition, calcium has importance as an intracellular secondary messenger, and it is known to participate in auxin, gibberellic acid GA, and abscisic acid ABA signaling to regulate fruit set and ripening, cell division and expansion, and fruit softening . However, the influence of calcium nutrition, transport and signaling pathways on fruit development and ripening still remains largely unclear …”
Section: Introductionmentioning
confidence: 99%